2017
DOI: 10.1002/j.1681-4835.2017.tb00596.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Telecentre Components on the Psychological Empowerment of Underserved Community Members in the Western Cape, South Africa

Abstract: ICTs and ICT4Ds are powerful socio-economic enablers within developing countries and provide members of "underserved" communities within these countries with tools for selfempowerment and circumvention of inequalities. Telecentres provide public access to ICTs to meet the educational, social, psychological and economic needs of a community. However, few studies have focused on the influence that telecentres have on the psychological empowerment of members of "underserved" communities in which they are situated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 64 publications
3
14
0
1
Order By: Relevance
“…Other findings showed that the model of managerial empowerment based on future components of research had a good fit and the categories of change management, empowerment, sense of competence, organizational structure, standardization and growth and improvement played a significant role in the model of empowerment of managers based on future components of research. These findings are in line with the findings of Karp et al (2020), Hassanzadeh KafshkarKalaei et al (2020), Hajizadeh & Hafezian (2019, Dortaj et al (2019), O'Hara & Clement (2018, and Osman & Tanner (2017). ), Niazazari & Taghvaei Yazdi (2014) and TaghipourZahir & Jahanian (2009) were consistent.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Other findings showed that the model of managerial empowerment based on future components of research had a good fit and the categories of change management, empowerment, sense of competence, organizational structure, standardization and growth and improvement played a significant role in the model of empowerment of managers based on future components of research. These findings are in line with the findings of Karp et al (2020), Hassanzadeh KafshkarKalaei et al (2020), Hajizadeh & Hafezian (2019, Dortaj et al (2019), O'Hara & Clement (2018, and Osman & Tanner (2017). ), Niazazari & Taghvaei Yazdi (2014) and TaghipourZahir & Jahanian (2009) were consistent.…”
Section: Discussionsupporting
confidence: 86%
“…O' Hara & Clement (2018) concluded that empowerment included decision-making power, creative thinking, critical thinking, and awareness rising. In another study, Osman & Tanner (2017) introduced the factors affecting psychological empowerment including intrapersonal, interactive and behavioral factors. In another study, Niazazari & Taghvaei Yazdi (2014) reported that empowering university administrators includes four structural approaches (vision, goals and mission of the university, university structure and policy, teaching methods and ways to acquire skills and knowledge, application of information and communication technology, and Suggestion system), managerial approach (increasing university productivity, building trust, commitment and acceptance of responsibility, continuous development and improvement of managers' performance, management and leadership strategies, and a sense of job security and satisfaction), motivational approach (creating motivation and self-esteem, respect and credibility To managers, self-esteem, self-confidence and self-fulfillment, payment and reward system and flexibility, self-control and self-evaluation) and participatory approach (freedom of action and autonomy, group participation and sharing of university information, individual decision-making in university, power sharing and delegation at levels University and ethics and professional behavior).…”
Section: Introductionmentioning
confidence: 99%
“…Through the 2016 White Paper, the government seeks to create a Digital Development Fund, the focus of which will be on universal access projects and universal service subsidies for members of identified segments of society (South Africa, DTPS, , p. 33). This implies an intent to continue with public access ICT4D programmes such as public information terminals or kiosks (Oyedemi, ; Stillman et al, ), multipurpose community centres (Gomez et al, ; Mbatha, ; Osman & Tanner, ), and free public Wi‐Fi (Du Bois & Chigona, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on a case study; identifies six amendments to the choice framework (Kleine, 2013) to enhance the usefulness of its application. Osman and Tanner (2017) Found that in telecentre programmes services, computer training and entrepreneurial support positively influence and contribute to the perceived psychological empowerment of "underserved" community members.…”
Section: Attwood and Maymentioning
confidence: 99%
“…Scholars have researched CTCs as spaces where people access ICTs in order to access information, develop skills, and use important services that promote (self-)development [19,20], health [21], literacy improvement [10,22], access to E-Government services [23], financial inclusion [24], tackling the digital age gap [25], and other utilitarian outcomes. Some practitioners have questioned the relevance of CTCs in the age of mobile internet, where smartphones and data plans are more and more accessible (see [15]).…”
Section: Theoretical Frameworkmentioning
confidence: 99%